EVALUATION OF THE QUALITY OF MULTIFUNCTIONAL COATINGS AND SELECTION OF BASIC REQUIREMENTS TO ENSURE OPERATIONAL RELIABILITY - Egamnazarova Fazilat Dostqobilovna (American Journals Publishing, 2022)
A lot of work is being carried out on the selection of research objects for the creation of effective organomineral materials and multifunctional coatings based on them using local raw materials. Production of high-quality coatings is a requirement of time.
Keywords: Paint, varnish, coating, electrolyte, insulation.